THE USE OF SURVEY APPLICATION TO CREATE LEARNING MODULES IN THE PANDEMIC ERA - Arinah Fransori; Nur Irwansyah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
Effective learning needs to be supported by adequate facilities and infrastructure that are approved in finding relevant references and materials. In the field, learning is quite difficult in the learning process because of limited referrals/material. Therefore, it is necessary to design a module that is by following the syllabus (RPS) that helps students learn independently. The purpose of the research is to find the needs and desires that are expected in the course modules in linguistic/literature research methods. The research method used was conducting a survey using questionnaires and conducting interviews. The questionnaire analyzes the needs of students and lecturers who are then analyzed by identifying based on their needs. The questionnaire for needs analysis is published with SurveyMonkey media application to facilitate the process of filling out the questionnaire. The results of the interview activities will be described qualitatively based on field observations. The subjects of the study were 100 students in the 6th semester and three lecturers who were lecturers parallel to this course. The results of this study consisted of an analysis of student needs and the views of the lecturers regarding the design content of the module, which contained; dimension of content, learning